Behavioral features and disorganization of oscillatory activity in C57BL/6J mice after acute low dose MK-801 administration - Cui, Keke; Yu, Zhipeng; Xu, Le; Jiang, Wangcong; Wang, Luwan; Wang, Xiangqun; Zou, Dandan; Gu, Jiajie; Gao, Feng; Zhang, Xiaoqing; Wang, Zhengchun (Frontiers in Neuroscience, 2022)
Low dose acute administration of N-methyl-D-aspartate receptor (NMDAR) antagonist MK-801 is widely used to model cognition impairments associated with schizophrenia (CIAS) in rodents. However, due to no unified standards for animal strain, dose, route of drug delivery, and the duration of administration, how different doses of MK-801 influence behavior and fundamental frequency bands of the local field potential (LFP) in cortical and subcortical brain regions without consistent conclusions. The optimal dose of MK-801 as a valid cognition impairers to model CIAS in C57BL/6J mice remains unclear. The current study characterizes the behavior and neural oscillation alterations induced by different low doses of MK-801 in medial prefrontal cortex (mPFC) and hippocampus CA1 of C57BL/6J mice. The results reveal that mice treated with 0.1 and 0.3 mg/kg MK-801 demonstrate increased locomotion and diminished prepulse inhibition (PPI), while not when treated with 0.05 mg/kg MK-801. We also find MK-801 dose as low as 0.05 mg/kg can significantly diminishes spontaneous alteration during the Y-maze test, suggesting impaired spatial working memory in mice. Additionally, the oscillation power in delta, theta, alpha, gamma and HFO bands of the LFP in mPFC and CA1 was potentiated by different dose levels of MK-801 administration. The observed sensitivity against spatial working memory impairment and neural oscillation at 0.05 mg/kg MK-801 suggest that 0.05mg/kg will produce changes in CIAS-relevant behavior without overt changes in locomotion and sensorimotor processing in C57BL/6J mice.